Effect of R-CHOP Chemotherapy on Creatinine Clearance in Diffuse Large B-Cell Lymphoma - Handhika Mustika; Willy Yusmawan; Rery Budiarti; Dwi Antono; Kanti Yunika (RSUP Dr. Kariadi, 2025)
BACKGROUND: Diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin's lymphoma (LNH). First-line therapy for DLBCL is a combination regimen of Rituximab, Cyclophosphamide, Hydroxydoxorubicin, Vincristine (Oncovin), and Prednisone (R-CHOP). The CHOP regimen causes acute kidney injury (AKI) directly or mediated by reactive oxygen species (ROS). AKI is associated with significant morbidity and mortality in cancer patients, including high mortality, increased hospitalization, and a lower cancer remission. AIM: Analyzing the effect of R-CHOP chemotherapy on creatinine clearance values ​​in DLBCL lymphoma patients METHOD: Analytical observational study with a retrospective design involved 38 patients diagnosed with DLBCL who underwent R-CHOP chemotherapy at RSUP dr. Kariadi Semarang. The independent variable of the study was the frequency of chemotherapy. The dependent variables of the study were serum creatinine levels and creatinine clearance which were measured in 4 phases, namely before, post 3x-, post 4x- and post 5x- R-CHOP chemotherapy. Analysis used the Friedman, T-dependent, and Wilcoxon tests. RESULT: The creatinine clearance value of DLBCL lymphoma patients before administering R-CHOP had a normal value with an average of 68.98 mL/min. The creatinine clearance value of DLBCL lymphoma patients after administering R-CHOP after 3x chemotherapy was found to be an average of 78.26 mL/min, after 4x chemotherapy the average was 75.50 mL/min and after 5x chemotherapy the average was 73.24 mL/min. There was a significant difference in creatinine clearance values ​​for DLBCL lymphoma patients before and after administration of R-CHOP (p=0.018). CONCLUSION: Administration of R-CHOP chemotherapy has a significant effect on the creatinine clearance value of DLBCL lymphoma patients.